THE STUDY OF THE PHARMACOLOGICAL ACTIVITY OF NEW MULTICOMPONENT SYSTEM AT THE TOXIC EFFECT OF ALCOHOL - N. V. Lamanova; V. A. Barinov; E. A. Rud'ko; A. V. Malinin (Разработка и регистрация лекарственных средств)
The pharmacological activity of the combined formulation including ethanol-induced narcosis was studied. It is shown that the daily use of the combined formulation on the background of subchronic alcohol intoxication prevents the development of resistance to ethanol and reduces ethanol-induced narcosis both at single and prolonged administration.